Ágora 2.0 - a nova praça de Homero: proposta de modelo de construção colaborativa com aplicação ao código de conduta - DIAS, Giselle Colins Pereira (2021)
The aim of this research is to propose a collaborative construction model applied to the organizations code of conduct. It is presented that compliance programs aim to establish organizational guidelines for detecting and remediating misconduct, systematizing internal control and audit mechanisms. The issue of the effectiveness of compliance in the organizational culture is exposed in view of the occurrence of corruption cases in large organizations that have applied the program. The approach adopted was the investigation of the code of conduct. The premise that the lack of adherence stems from the traditional way of elaborating a regulation, a top-down model inherently characterized by the anti-democratic logic “issued by the few and destined for the many” was assumed. A sample mapping of the structure of compliance programs and codes of conduct was used to verify the state of the art, converging and diverging points. Qualitative research was carried out as a data survey strategy to assess the level of knowledge for the collaborative construction of the code of conduct. Based on the data obtained, it was concluded that there is a pre-disposition for collaborative work, although in practice there are no concrete ways to make it feasible. It is then proposed as an alternative a collaborative update model of the code of conduct based on a wiki tool and on the collaborative architecture of the Linux operational system, aiming at appropriation by the target audiences and based on the premise that the effectiveness of a rule stems from the belief and confidence in its correctness and a dialogical process in which communication will act transversally throughout the process.